Postmodern University Understanding: organizational and managerial aspects - Olga Boyko; Nina Svitaylo (Вісник Київського національного університету культури і мистецтв. Серія: Менеджмент соціокультурної діяльності, 2019)
Introduction. In the modern world, the university acquires new characteristics and functions, where traditional values are complemented by new ones which are connected with development of the regional community and entry to the international level. That is why the postmodern university should reorient its managerial and organizational levers. Purpose and methods. The purpose of the article is to consider the university as a driver of regional development through the analysis of its modern management. The study of postmodern university requires the use of multidisciplinary socio-cultural, structural and functional approaches and historical, analytical, comparative methods. Results. Universities that have always strived not only for knowledge for the sake of knowledge, but also for reproduction of knowledge for the sake of growth and strengthening of society well-being, must change the managerial paradigm. And such postmodern education institutions can be drivers of socio-economic development and scientific-educational potential. Conclusions and discussion. Modern universities have to become the growth points of the regions and take an active part in solving educational, socio-economic and cultural issues. Management of higher school should be aimed at ensuring its competitiveness both in the internal and external markets of educational services. The scientific novelty of the obtained results is to determine the factors of development of the postmodern university as a driver of growth of economy and socio-cultural sphere of the region. The practical significance of the obtained results is reflected in the possibility of using the idea of the university as a point of growth of the region and the country.